2017
DOI: 10.3847/1538-4357/aa99de
|View full text |Cite
|
Sign up to set email alerts
|

iPTF 16asu: A Luminous, Rapidly Evolving, and High-velocity Supernova

Abstract: Wide-field surveys are discovering a growing number of rare transients whose physical origin is not yet well understood. Here we present optical and UV data and analysis of intermediate Palomar Transient Factory (iPTF) 16asu, a luminous, rapidly evolving, high-velocity, stripped-envelope supernova (SN). With a rest-frame rise time of just fourdays and a peak absolute magnitude of M 20.4 g = -mag, the light curve of iPTF 16asu is faster and more luminous than that of previous rapid transients. The spectra of i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(124 citation statements)
references
References 111 publications
5
119
0
Order By: Relevance
“…Again, this indicates that a strict luminosity cutoff is not a suitable way to select SLSNe. We also note that the peak luminosities of our faintest SLSNe are comparable to some of the most luminous Type Ic-BL SNe discovered (e.g., Sanders et al 2012;Whitesides et al 2017), suggesting that there is not a true luminosity "gap" between SLSNe and core-collapse SNe.…”
Section: Luminosity Function Of H-poor Slsnementioning
confidence: 69%
“…Again, this indicates that a strict luminosity cutoff is not a suitable way to select SLSNe. We also note that the peak luminosities of our faintest SLSNe are comparable to some of the most luminous Type Ic-BL SNe discovered (e.g., Sanders et al 2012;Whitesides et al 2017), suggesting that there is not a true luminosity "gap" between SLSNe and core-collapse SNe.…”
Section: Luminosity Function Of H-poor Slsnementioning
confidence: 69%
“…For some luminous and rapidly evolving transients such as iPTF16asu (Whitesides et al 2017), and AT 2018cow (Prentice et al 2018b), powering through the spin down of a magnetar has been investigated. Since LSQ13ddu also displays a fast rise and high peak luminosity, we have tested if LSQ13ddu could be fit by a magnetar model.…”
Section: Photometric Modelling Of Magnetar Poweringmentioning
confidence: 99%
“…Some rapidly evolving transients such as iPTF16asu (Whitesides et al 2017) have been investigated to see if their light curve could be powered by magnetar formation but it was found that the derived ejecta masses were too low (e.g. Arcavi et al 2016).…”
Section: The Potential Progenitor System Of Lsq13ddumentioning
confidence: 99%
“…INTEGRAL observations contributed to the triangulation, which allowed for establishing the association between GRB170105 and ATLAS17aeu (Svinkin et al 2017a). In general, INTEGRAL data are particularly useful to retrospectively search for GRB events, owing to its competitive and consistent omnidirectional sensitivity, stable background, and high duty cycle (see, e.g., a recent case studied by Whitesides et al 2017). GRB170105 was later found to be likely unrelated to GW170104 Stalder et al 2017).…”
Section: Integral Observations Of Gw170104mentioning
confidence: 99%